Pengaruh Partai Politik Bagi Pendidikan Politik Pemilih Pemula Pada Pemilihan Walikota Kota Medan Tahun 2020 - Benito Asdhie Kodiyat MS; Andryan Andryan (Universitas Medan Area, 2021)
The implementation of decentralization will be successful if the process of determining regional heads is not in the shadow of the national political elite. More broadly, this did not provide an opportunity for people in the city of Medan to freely determine their future leader. At some level, such a process would destroy regional democratization. Therefore, the problem to be examined is how the influence of the centralization of political party policies in relation to the election and determination of regional head candidates carried out by political parties, we need to discuss in advance what causes the direct implementation of regional head elections and how the role of political parties in recruiting candidates. District head. The research method used is normative legal research. The results show that the regional head elections that have undergone a shift from indirect elections in the DPRD to direct elections by the people have constructive consequences for democracy and the concept of people's sovereignty in the context of elections and the role of political parties which are very strategic because they are able to carry regional head candidates to become head candidates. regions in regional head elections experience conceptual ambivalence, and also political parties have a dominant influence on first-time voters in the 2020 Medan mayoral election